PATTERNS OF INMATE DEVELOPMENT BASED ON PAPUAN CULTURE AND LOCAL WISDOM IN CLASS IIA ABEPURA PRISON - Yuska, Syahrial; Orisu, Terry Urick (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to analyze the pattern of coaching prisoners based on Papuan culture and local wisdom in the Class IIA Abepura prison. The method used in this research is descriptive qualitative, with an observation, interview, and documentation approach. The research results show that the development program at the Class IIA Abepura Prison includes two main categories: the Personality Development Program and the Independence Development Program, which focuses on local cultural values ​​as a means of rehabilitation and reintegration. Local culture and wisdom are proven to play an important role in increasing inmates' involvement, identity, and motivation to change. However, challenges such as cultural diversity, limited resources, resistance, and lack of coordination become obstacles in implementing the program. To overcome these challenges, strategic steps such as staff training, increased collaboration, and the development of evaluation metrics are needed. The research conclusions confirm the importance of a culture-based approach to increase the effectiveness of development programs and support the reintegration of prisoners into society. Keywords: Prisoner Development; Local Culture; Local Wisdom; Social Reintegration